2023
DOI: 10.1021/acs.analchem.2c05084
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Separation and Enrichment of Escherichia coli by Size Using Viscoelastic Flows

Abstract: Here, we achieve the separation and enrichment of Escherichia coli clusters from its singlets in a viscoelastic microfluidic device. E. coli, an important prokaryotic model organism and a widely used microbial factory, can aggregate in clusters, leading to biofilm development that can be detrimental to human health and industrial processes. The ability to obtain high-purity populations of E. coli clusters is of significance for biological, biomedical, and industrial applications. In this study, polystyrene par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Therefore, a sample throughput as high as 120 μL min −1 was reported in our device, which was much higher than that of previous work using PEO as the elastic enhancer. 29–32 The good biocompatibility of HA solution was well validated in many previous studies. 36…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Therefore, a sample throughput as high as 120 μL min −1 was reported in our device, which was much higher than that of previous work using PEO as the elastic enhancer. 29–32 The good biocompatibility of HA solution was well validated in many previous studies. 36…”
Section: Resultsmentioning
confidence: 70%
“…As compared with single-phase viscoelastic microfluidics, the interfacial viscoelastic microfluidics offers an improved performance for cell separation by using a co-flowing system. 29 Currently, the interfacial viscoelastic microfluidics is successfully applied to separate Escherichia coli clusters from their singlets, 30 circulating tumor cells from background blood cells, 31,32 and large extracellular vesicles from small exosomes. 33,34 As can be seen from the above progress, great successes have been achieved in the field of viscoelastic microfluidics.…”
Section: Introductionmentioning
confidence: 99%
“…μFAE is a type of passive force‐assisted extraction/separation method, by driving analyte passing through specific channel structures with the inherent fluid effect in microscale, including laminar co‐flow [33], Dean flow [52], viscoelastic flow [53, 54], and inertial migration [34, 36, 37]. For example, Wang et al.…”
Section: Microfluidic Sample Preparation Techniquesmentioning
confidence: 99%
“…μFAE is a type of passive force-assisted extraction/separation method, by driving analyte passing through specific channel structures with the inherent fluid effect in microscale, including laminar co-flow [33], Dean flow [52], viscoelastic flow [53,54], and inertial migration [34,36,37]. For example, Wang et al [33] reported the μFAE of Mg(OH) 2 from seawater by laminar co-flow-induced nonequilibrium, which avoids the interference of coexisted Ca 2+ easily happens in conventional seawater Mg extractions.…”
Section: Microfluidic Field-assisted Extraction Techniquesmentioning
confidence: 99%
“…Moreover, the introduced external forces like the mechanical kicking force generated from the cavitation bubbles can seriously damage biological samples, e.g., mammalian cells . The passive approaches such as hydrophoresis, deterministic lateral displacement (DLD), viscoelastic microfluidics, and inertial microfluidics are available for particle separation . However, hydrophoresis requires additional functional microstructures within the microchannel, DLD suffers from lifetime fouling and clogging and viscoelastic microfluidics asks for the specific non-Newtoninan solutions like polyethylene oxide medium. , Inertial microfluidics, which works at intermediate Reynolds numbers (∼1 < Re < ∼100), is prominent in precise particle control and high throughput, thus being widely used for particle separation …”
Section: Introductionmentioning
confidence: 99%